The genome sequence of wild privet, Ligustrum vulgare L. [version 1; peer review: 1 approved, 2 approved with reservations] - Michelle L. Hart; David Bell; Vladimir Krivtsov; Zoë A. Goodwin (Wellcome Open Research)
We present a genome assembly from a specimen of Ligustrum vulgare (wild privet; Streptophyta; Magnoliopsida; Lamiales; Oleaceae). The genome sequence has a total length of 1,384.00 megabases. Most of the assembly is scaffolded into 23 chromosomal pseudomolecules. The multipartite mitochondrial genome consists of two circularised molecules with lengths of 844.62 and 118.10 kilobases, and the plastid genome assembly is 161.82 kilobases long. Gene annotation of this assembly on Ensembl identified 31,482 protein-coding genes.